Design, Modeling and Hardware Implementation of Regenerative Braking for Electric Two-Wheelers for Hilly Roads - Tako Nama; Prosenjit Mondal; Praveen Tripathy; Ravindranath Adda; Anup Kumar Gogoi (IEEE Access, 2022)
The electric vehicles which operate in hilly region gain potential energy while moving uphill. Some of this energy can be recuperated to charge the battery while the vehicle moves downhill by using regenerative braking. The speed of the electric vehicle while descending the slope of hilly roads is often low to ensure the safety of the passenger, hence requiring regenerative braking at low speed. Braking at low speed is quite challenging due to the low level of back electromotive force (EMF) during regenerative braking. This paper presents a modular regenerative braking circuit for electric scooters operating at low speeds. The proposed modular regenerative braking circuit’s configuration, operation, and control scheme are explained in the paper. Here using the state-space averaging technique, the small-signal modeling of the braking circuit was done, and a Type-II current controller was designed to track the braking current reference. The proposed configuration also suggests fast switching between the motoring and regenerative modes by enabling or disabling the gate pulses to the inverter or DC/DC boost converter. This removes the need for a separate switch in the power circuit, hence increasing reliability and reducing cost. The operation of the proposed regenerative braking circuit, along with the overall motor drive-train of the vehicle, was simulated in MATLAB/Simulink. Its hardware implementation was conducted on a scaled-down laboratory test set-up. The simulation and experimental results verify the working of the proposed regenerative braking circuit and the effectiveness of the proposed control scheme.